2020
DOI: 10.1002/mop.32495
|View full text |Cite
|
Sign up to set email alerts
|

Different implementations of material independent multi‐order nearly perfectly matched layers for EM simulations

Abstract: To deal with EM simulations with the low‐frequency evanescent and propagation waves, multi‐order nearly perfectly matched layers (NPML) with complex frequency shifted factor are presented to terminate finite‐difference time‐domain (FDTD) domains. By incorporating the digital signal processing techniques including the bilinear Z‐transform, matched Z‐transform, and direct Z‐transform methods, the proposals can not only obtain better performance compared with the original NPMLs but also have considerable efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…It can be concluded that the proposed algorithm holds the best performance from the aspect of accuracy. Such conclusion can be further demonstrated by the relative local error and relative error in the time and frequency domain, respectively 33 . The relative local error can be defined as RitalicdBt=20log10EttEbtmaxEbt where Ett is the test solution which can be obtained directly by employing different algorithms and Ebt is the basis for comparison.…”
Section: Numerical Results and Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It can be concluded that the proposed algorithm holds the best performance from the aspect of accuracy. Such conclusion can be further demonstrated by the relative local error and relative error in the time and frequency domain, respectively 33 . The relative local error can be defined as RitalicdBt=20log10EttEbtmaxEbt where Ett is the test solution which can be obtained directly by employing different algorithms and Ebt is the basis for comparison.…”
Section: Numerical Results and Discussionmentioning
confidence: 92%
“…In order to maintain the stability of the algorithm, time step is chosen according to the fine mesh as Δt=0.95Δ/2c0=15.8 fs. Absorption of PML regions can be reflected by the relative reflection error in the time domain, as shown in Figure 3 33 …”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original higher-order formulation holds six auxiliary variables which affect the efficiency and absorption [ 32 ]. Alternative higher-order formulation with four auxiliary variables is introduced to improve the entire performance, which has been extensively employed in massive problems [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…As can be concluded that they ae based on the first order formulation whose absorption problem still exist in the low-frequency band and late-time reflections. To alleviate such condition, the higher order concept is incorporated into the PML regions for the development higher order PML regions into the simulation of GPR problems [24][25][26]. The increment of coefficients and matrices leads to the significant decrement of efficiency.…”
Section: Introductionmentioning
confidence: 99%